PENINGKATAN PEMAHAMAN ETIKA PELAYANAN KONSUMEN UNTUK MENINGKATKAN PENGHASILAN DAN KETAHANAN SOSIAL - Bagus Haryono; Argyo Demartoto; Rahesli Humsona; Brq Dagfa Inka Mahadika (Aptekmas Jurnal Pengabdian pada Masyarakat, 2022)
This service aims to increase understanding of consumer service ethics for online food drivers to increase their income and social resilience in the Covid 19 Era. We brought together the dimensions of education and sociology, as well as an analysis of the theories of Emile Durkheim, Bloom, Paulo Freire, and Karl Marx. The subjects were online food drivers, who were determined by purposive sampling based on variations in the type of food and the distance of delivery. To increase the understanding of service ethics, the method of lectures, making videos, and playing it in the community. Process awareness and cooperation are applied to enact agreed ethics for the sake of simultaneously, moral education avoiding fraudulent behavior, establishing social harmony, obeys consumer laws and partnerships. The location is chosen in the area of the delivery range a maximum of 5-kilo meters from the basecamp. After being given an ethical understanding in service to consumers, drivers are proven to always pay attention to buyer records to them and online stalls. Consequently, they always get a high rating, still, get incentives, and increase their income, to avoid termination of partners. Mentoring has resulted in regulatory agreements to avoid fraudulent behavior that has the potential to give rise to disintegration, and the establishment of social harmony, as well as further strengthening its social resilience in the Covid 19 Era.